FLIGHT HOURS AND BMI AGAINST TUC IN HYPOBARIC CHAMBER ALTITUDE 25.000 FEET - Nuralfilail, Zakiah Nada; Savitri, Pritha Maya; Hardini, Niniek; Chairani, Aulia; Andriyanto; Budi Maryoto, Agus; A., Samsul; Kardiana, Yaya; Cakrahaya, Agus (Journal of Vocational Health Studies, 2024)
Background: Time of Useful Consciousness (TUC) is the time interval a person can survive carrying out flight duties due to a decrease in oxygen pressure and the point at which there is a decrease in the level of consciousness. The TUC time interval is influenced by various factors including Body Mass Index (BMI) and flying hours which affect the increase in the duration of the body's exposure to hypoxic conditions in pilots. Purpose: This research was conducted to determine the relationship between total flight hours and BMI on TUC. Method: This research employed observational analytic research with a cross-sectional method. Sampling was taken by simple random sampling technique. The sample for this research included active flight crew members from Lakespra dr. Saryanto 202 who met the inclusion criteria. Result: There were 53 research subjects, with the results showing that 48 subjects (90.6%) had a TUC <4 minutes, and 5 subjects had a TUC >4 minutes. There were 47 subjects (88.7%) with total flight hours >1000 hours and 6 subjects (11.3%) with total flight hours <1000 hours. In BMI, 37 subjects (69.8%) had an overweight BMI, and 16 subjects (30.2%) had a normal BMI. Conclusion: After examining 53 subjects, it was found that there was no relationship between total flight hours and TUC (p-value = 1.000) or BMI and TUC( p-value = 0.307) in the hypobaric chamber at an altitude of 25.000 feet.